Emerging nanotechnology applications in electrical engineering - Mohamed, Ahmed Thabet, 1974- (Advances in computer and electrical engineering (ACEE) book series., 2021)
"This book is a collection of innovative research on the methods and application of nanoparticles in electrical engineering that discusses the wide array of uses nanoparticles have within electrical engineering and the diverse electric and magnetic properties that nanomaterials help make prevalent"--